Awareness and Practice of Family Planning Methods among Women in Jumla - A Cross-Sectional Study - Shahi, Nabina; Timalsina, Indira (Journal of Karnali Academy of Health Sciences, 2023)
Background: The family planning method is used to help individuals and couples to avoid unwanted pregnancies, regulate intervals between pregnancies, and determine the number of children to be given birth. Its acceptability and utilization is affected by many factors, and an important one is lack of knowledge. This study is aimed to assess the awareness and practice of family planning methods among women in Chandannath Municipality, Jumla. Methodology: A community-based descriptive cross-sectional study was conducted through face-to-face interviews using a semi-structured interview questionnaire among 64 women. The Multi-stage sampling technique was adopted. The study site was selected by simple random sampling within the Chandannath municipality. The sample was selected by systematic random sampling technique. Ethical approval was taken from the IRC of Karnali Academy of Health Sciences. Data were analyzed by using SPSS_16. Results: Out of 64 respondents, 31.30% were >40 years. 96.90% respondents and 98.40% of their husbands were literate. 60.90% had family size below five, and 89.10% had <3 children. 59.37% respondents understand family planning as a measure of birth control. 62.50% were aware that FP improves maternal and child health. 79.6% had information from health workers. 90.60% respondents were aware that family planning methods are available from health posts. Out of 46.90% family planning method users, 36.65% used Depo-Provera. Conclusion: This study demonstrates that more than half of the respondents had adequate awareness and nearly half of the respondents were current family planning users. There is no association between the awareness level and practice of family planning.